Postsynaptic mechanisms render syn I/II/III mice highly responsive to psychostimulants - Pogorelov, Vladimir M. (2019)
Background:Synapsins are encoded by SYN I, SYN II, and SYN III, and they regulate neurotransmitter release by maintaining a reserve pool of synaptic vesicles. Methods:Presynaptic dopamine responses to cocaine were examined by microdialysis, and postsynaptic responses were evaluated to various dopamine receptor agonists in the open field with SynI/SynII/SynIII triple knockout mice. Results:Triple knockout mice showed enhanced spontaneous locomotion in a novel environment and were hyper-responsive to indirect and direct D1 and D2 dopamine agonists. Triple knockout animals appeared sensitized to cocaine upon first open field exposure; sensitization developed across days in wild-type controls. When mutants were preexposed to a novel environment before injection, cocaine-stimulated locomotion was reduced and behavioral sensitization retarded. Baseline dopamine turnover was enhanced in mutants and novel open field exposure increased their striatal dopamine synthesis rates. As KCl-depolarization stimulated comparable dopamine release in both genotypes, their readily releasable pools appeared indistinguishable. Similarly, cocaine-induced hyperlocomotion was indifferent to blockade of newly synthesized dopamine and depletion of releasable dopamine pools. Extracellular dopamine release was similar in wild-type and triple knockout mice preexposed to the open field and given cocaine or placed immediately into the arena following injection. Since motor effects to novelty and psychostimulants depend upon frontocortical-striatal inputs, we inhibited triple knockout medial frontal cortex with GABA agonists. Locomotion was transiently increased in cocaine-injected mutants, while their supersensitive cocaine response to novelty was lost. Conclusions:These results reveal presynaptic dopamine release is not indicative of agonist-induced triple knockout hyperlocomotion. Instead, their novelty response occurs primarily through postsynaptic mechanisms and network effects.